THEOLOGICAL EDUCATION IN RUSSIA TODAY - Alekseev, Anatoly (2014)
The paper includes three parts: The first part gives a survey about Theological education in Russia before the Communist revolution of 1917. The second part deals with the revival of Theological education, which started on a very low level with the refounding of the Spiritual Academies in 1944 and continued with the celebrations of the millenium of Christianity in Russia in the eighties. But only after 1989 it became possible to reestablish theologicy as an Academic discipline and to found new institutions. Most of them are Church-institutions; and even today only very few are on an Academic level according to international standards. One of them is the Biblical Institute of the Philological Faculty of St. Petersburg State University, whose activities are described in the third section of the paper.
Keywords: Spiritual Academy; Russia; Orthodox; Education; Bibliotheca Biblica; Biblical Philology